Kewenangan Pemerintah Dalam Pengadaan Tanah untuk Kepentingan Swasta berdasarkan Undang-Undang Nomor 2 Tahun 2012 tentang Pengadaan Tanah Bagi Pembangunan untuk Kepentingan Umum - Ikma Hendra Putra; Djumardin Djumardin; Widodo Dwi Putro (Departement of Mathematics Education, 2023)
This research aims to find out the authority and process and mechanism of land acquisition for private interests in terms of building the smelter facility of PT. Amman Mineral Nusa Tenggara (AMMAN) in the industrial area of Maluk Village, Maluk District, West Sumbawa Regency which is a National Strategic Project regulated in the Presidential Regulation of the Republic of Indonesia Number 18 of 2020 concerning the 2020-2024 National Medium Term Development Plan. In carrying out the development agenda (national priority) of the 2020-2024 RPJMN, Strategic Priority Projects (Major Projects) are prepared, namely 9 industrial areas outside Java and 31 smelters. In this regard, in terms of solving problems or answering problems, empirical normative types are used by using 3 approaches, namely the Conceptual Approach, the Statute Approach and the case approach by collecting data which includes data Primary and secondary data were studied and analyzed using qualitative-descriptive analysis. By using this method, the author is finally able to answer the existing problems, namely land acquisition for private interests in terms of the construction of PT. Amman Mineral Nusa Tenggara (AMMAN) based on Law Number 2 of 2012 concerning Land Acquisition for Public Interest for the construction of a smelter is carried out through 4 stages, namely the planning stage, the preparation stage, then the implementation stage and the results delivery stage. As for the process of implementing compensation for land acquisition for the public interest, the construction of the smelter PT. AMNT starts from the stages of inventory and identification of land tenure, ownership, use and utilization. After the inventory was carried out, the implementing team then carried out an assessment of compensation for community land which included the area of land required in this land acquisition.